Fabrication and In Vitro Study of Tissue-Engineered Cartilage Scaffold Derived from Wharton's Jelly Extracellular Matrix. (29th October 2017) - Xiao, Tongguang; Guo, Weimin; Chen, Mingxue; Hao, Chunxiang; Gao, Shuang; Huang, Jingxiang; Yuan, Zhiguo; Zhang, Yu; Wang, Mingjie; Li, Penghao; Peng, Jiang; Wang, Aiyuan; et al.
Abstract : The scaffold is a key element in cartilage tissue engineering. The components of Wharton's jelly are similar to those of articular cartilage and it also contains some chondrogenic growth factors, such as insulin-like growth factor I and transforming growth factor- β . We fabricated a tissue-engineered cartilage scaffold derived from Wharton's jelly extracellular matrix (WJECM) and compared it with a scaffold derived from articular cartilage ECM (ACECM) using freeze-drying. The results demonstrated that both WJECM and ACECM scaffolds possessed favorable pore sizes and porosities; moreover, they showed good water uptake ratios and compressive moduli. Histological staining confirmed that the WJECM and ACECM scaffolds contained similar ECM. Moreover, both scaffolds showed good cellular adherence, bioactivity, and biocompatibility. MTT and DNA content assessments confirmed that the ACECM scaffold tended to be more beneficial for improving cell proliferation than the WJECM scaffold. However, RT-qPCR results demonstrated that the WJECM scaffold was more favorable to enhance cellular chondrogenesis than the ACECM scaffold, showing more collagen II and aggrecan mRNA expression. These results were confirmed indirectly by glycosaminoglycan and collagen content assessments and partially confirmed by histology and immunofluorescent staining. In conclusion, these results suggest that a WJECM scaffold may be favorable for future cartilage tissue engineering.